Multitarget Molecular Imaging in Metastatic Castration Resistant Adenocarcinoma Prostate Cancer with Therapy Induced Neuroendocrine Differentiation - Joel Vargas Ahumada; Sofía D. González Rueda; Fabio A. Sinisterra Solís; Quetzali Pitalúa Cortés; Liliana P. Torres Agredo; Jimenez Ríos Miguel; Anna Scavuzzo; Irma Soldevilla-Gallardo; Miguel A. Álvarez Avitia; Nora Sobrevilla; Francisco Osvaldo García Pérez (Diagnostics, 2022)
Neuroendocrine differentiation of prostate cancer (NEDPC) includes de novo presentation and secondary to epigenetic changes, referred as therapy-induced neuroendocrine prostate cancer (t-NEPC). Molecular imaging with prostate-specific membrane antigen (PSMA) and somatostatin analogues positron emission tomography (PET/CT) in NEDPC have not been validated. 18F-FDG (fluorodeoxyglucose) PET/CT has numerous limitations in prostate cancer (PCa) and the utility in NEDPC has only been reported in a few series of cases. The objective of this study is to compare the lesions detection rate of the three radiotracers in metastatic t-NEPC patients. (1) Material and Methods: Retrospective evaluation of patients with prostate adenocarcinoma treated with androgen deprivation therapy, chemotherapy, a novel androgen receptor pathway inhibitor or a combination of them and a second tumour biopsy confirming t-NEPC was made. All patients underwent 18F PSMA-1007, 18F AlF-NOTA-Octreotide, and 18F-FDG PET/CT. Evaluation of positive lesions was determined and SUVmax of each radiotracer was estimated and correlated with computer tomography (CT) findings. (2) Results: A total of eight patients were included. The mean time from diagnosis of prostate adenocarcinoma to t-NEPC was 28.2 months, with a mean serum specific prostate antigen (PSA) of 16.6 ng/dl at the time of NEPC diagnosis. All patients were treated with antiandrogen therapy and 87.5% with chemotherapy. A total of 273 lesions were identified by CT from which 182 were detected by 18F-FDG PET/CT, 174 lesions by 18F PSMA-1007, and 59 by 18F AlF-NOTA-Octreotide. An interpatient analysis of the lesions was performed and dual tracer 18F-FDG PET/CT and 18F PSMA-1007 PET/CT detected a total of 270/273 lesions (98.9%). (3) Conclusions: NEDPC patients demonstrated wide inter and intrapatient molecular imaging heterogeneity within the three radiotracers. 18F-FDG detected most lesions in t-NEPC among all radiotracers, especially in visceral sites; 18F PSMA-1007 detected more bone lesions. 18F AlF-NOTA-Octreotide showed no significant utility.